Environmental noise pollution and risk of preeclampsia. (August 2018) - Auger, Nathalie; Duplaix, Mathilde; Bilodeau-Bertrand, Marianne; Lo, Ernest; Smargiassi, Audrey
Abstract: Background: Environmental noise exposure is associated with a greater risk of hypertension, but the link with preeclampsia, a hypertensive disorder of pregnancy, is unclear. Objectives: We sought to determine the relationship between environmental noise pollution and risk of preeclampsia during pregnancy. Methods: We analyzed a population-based cohort comprising 269, 263 deliveries on the island of Montreal, Canada between 2000 and 2013. We obtained total environmental noise pollution measurements (LAeq24, Lden, Lnight ) from land use regression models, and assigned noise levels to each woman based on the residential postal code. We computed odds ratios (OR) and 95% confidence intervals (CI) for the association of noise with preeclampsia in mixed logistic regression models with participants as a random effect, and adjusted for air pollution, neighbourhood walkability, maternal age, parity, multiple pregnancy, comorbidity, socioeconomic deprivation, and year of delivery. We assessed whether noise exposure was more strongly associated with severe or early onset preeclampsia than mild or late onset preeclampsia. Results: Prevalence of preeclampsia was higher for women exposed to elevated environmental noise pollution levels (LAeq24h ≥ 65 dB(A) = 37.9 per 1000 vs. <50 dB(A) = 27.9 per 1000). Compared with 50 dB(A), an LAeq24h of 65.0 dB(A) was not significantly associated the risk of preeclampsia (OR 1.09, 95% CI 0.99–1.20). Associations were however present with severe (OR 1.29, 95% CI 1.09–1.54) and early onset (OR 1.71, 95% CI 1.20–2.43) preeclampsia, with results consistent across all noise indicators. The associations were much weaker or absent for mild and late preeclampsia. Conclusions: Environmental noise pollution may be a novel risk factor for pregnancy-related hypertension, particularly more severe variants of preeclampsia. Graphical abstract: Image 1 Highlights: Noise exposure is a risk factor for cardiovascular disease in adult populations. We studied the association between noise and preeclampsia in pregnancy. Exposure to environmental noise was associated with a greater risk of preeclampsia. The associations were stronger for severe and early onset preeclampsia. Environmental noise may be a novel risk factor for preeclampsia in pregnant women. Abstract : This large population-based study of environmental noise pollution in a Canadian urban area suggests that noise exposure may be a novel risk factor for preeclampsia, particularly more severe variants of preeclampsia.